Вплив діаметра та об'ємної частки армуючих елементів на формування композиційних виливків - Тарасевич, М.І.; Шинський, О.Й.; Шалевська, І.А.; Корнієць, І.В.; Гнилоскуренко, С.В.; Дьяченко, М.М. (Physico-technological Institute of Metals and Alloys, 2025)
For modern machinery, composite materials are of great importance because they ensure improved properties of parts. The work is dedicated to study the influence of the diameter and volume fraction of the reinforcement elements in the form of rods on the thermal processes that occur during the crystallization and structure formation of cast steel composites. Computational experiment and computer modeling were used to study the thermal interaction between the matrix melt (steel 35) and reinforcing elements (steel 20), phase transformation at their different diameters (2-10 mm) and volume fraction (10-50 %), the formation and growth dynamics of solid crusts at the interface between the “melt – reinforcing element” phases and the critical parameters that ensure optimal connection of the matrix alloy with the reinforcing elements. As a result a critical relationship of the diameter and volume fraction of the reinforcing elements (18–31.5 %) was established, which influences the quality of adhesion (bonding) between phases and the microstructure of the material. Regression models have been developed to predict temperature regimes on the surface of reinforcing elements depending on their diameter and volume fraction and the optimal technological parameters for obtaining composite castings have been determined. With diameters of reinforcing elements of 2-5 mm, their volume fraction of 10-50 % complete melting of the reinforcing phase occurs, which ensures homogenization of the structure. For rod diameters of 6-10 mm their critical (or maximum) volume fractions are indicated for 7 mm — 21 %, for 9 mm — 16 %, in which optimal phase connection is achieved without creating a stable solid crust. The practical significance of these results lies in the possibility of precise control and optimization of technological parameters when obtaining high-quality cast composites with minimal defects.